OPTIMALISASI PELAYANAN MELALUI PROGRAM SEDERHANA SEKALI URUS ADMINISTRASI KEPENDUDUKAN (NASI UDUK) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN INDRAGIRI HILIR TAHUN 2021 - Febri Wahyuni; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Digital-based public services are one of the efforts to overcome the limitations of direct public services as well as a solution in order to prevent the transmission of Covid-19, so that digital innovation is needed in public services to remain effective and efficient. This research was conducted to find out and describe the implementation of the Simple Program for Managing Population Administration (NASI UDUK) in optimizing services at the Department of Population and Civil Registration of Indragiri Hilir Regency in 2021. This research is a descriptive qualitative research. The data collection techniques in this study are using interviews, observation and documentation. This research analysis uses five indicators of public service innovation according to Rogers, namely: relative advantage, compability, complexity, triability and observability. The results of the study show that Optimizing Services Through the Simple Program for Managing Population Administration (NASI UDUK) in general has been going well and is acceptable to the community, but timeliness, socialization and how to use services are obstacles in implementing this innovation, so that this innovation cannot be said effective and efficient. Keywords : Relative Advantage, Compability, Complexity, Triability, Observability